Herbs and Spices 2020
DOI: 10.5772/intechopen.92676
|View full text |Cite
|
Sign up to set email alerts
|

Rhus coriaria (Sumac): A Magical Spice

Abstract: Rhus coriaria L. (Sumac) has been used as folk medicine since ancient times. Rhus genus has over 91 of accepted species names in the Anacardiaceae family, Rhus coriaria L. is the only species in Iraq that growth wildly and/or cultivated near the villages in the north of Iraq. It has a characteristic taste and morphological features, making it to be considered as one of the popular flavoring spice, drink, appetizer, and as acidulant in food recipes, in addition to its role as plant medicine. A scrutiny of liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Nowadays, corticosteroids, including triamcinolone acetonide are considered as the preferred and conventional [ 6 ] treatment option for lichen planus [ 7 – 9 ] since they can relieve the signs and symptoms through lowering the inflammation of the lesion [ 10 , 11 ]. Moreover, it was found that 0.1% triamcinolone acetonide orabase can repair the imbalance of oxidation/antioxidation condition in the oral environment which is considered as a contributing factor in developing the oral lichen planus condition [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, corticosteroids, including triamcinolone acetonide are considered as the preferred and conventional [ 6 ] treatment option for lichen planus [ 7 – 9 ] since they can relieve the signs and symptoms through lowering the inflammation of the lesion [ 10 , 11 ]. Moreover, it was found that 0.1% triamcinolone acetonide orabase can repair the imbalance of oxidation/antioxidation condition in the oral environment which is considered as a contributing factor in developing the oral lichen planus condition [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…With its various geographical climates, Iran presents appropriate conditions for the growth of Rhus coriaria [ 5 ]. This plant has been used in herbal medicine due to its various properties such as antimicrobial, antioxidant, hypoglycemic, hypolipidemic, antimutagenic, antimigratory, and anti-ischemic activities [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can decrease stomach acid due to its high tannin, flavonoid, organic acid, protein, fiber, sal volatile, nitrate, nitrite, and antioxidant content ( 18 ). The R. coriaria fruit is used as a disinfectant for the treatment of constipation and for the reduction of serum triglyceride levels, blood pressure, and uric acid ( 19 ). AgNPs are used for the treatment of infectious diseases due to optimal antibacterial effects ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Its main exporters are Iran and Syria [6]. There is a growing interest in the use of this important seasoning in medicine and the food industry [7]. Its aqueous extract has a Disclaimer/Publisher's Note: The statements, opinions, and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s).…”
Section: Introductionmentioning
confidence: 99%